Toward Food Sovereignty for Coastal Communities of Eastern Québec: Co-designing A Website to Support Consumption of Edible Resources from the St. Lawrence River, Estuary, and Gulf. Issue 1 (April 2022) - Fallon, Catherine; Lemire, Mélanie; Dumont, Dany; Parent, Elizabeth; Figueroa, Esteban; Cummings, Isabelle; Brousseau, Julie; Marquis, Marie; Paquet, Nicolas; Plante, Steve; Witteman, Holly O.
Background. Despite the abundance and proximity of edible marine resources, coastal communities along the St. Lawrence in Eastern Québec rarely consume these resources. Within a community-based food sovereignty project, Manger notre Saint-Laurent ("Sustenance from our St. Lawrence"), members of participating communities (3 non-Indigenous, 1 Indigenous) identified a need for a web-based decision tool to help make informed consumption choices.Methods. We thus aimed to co-design a prototype website that facilitates informed choices about consuming local edible marine resources based on seasonal and regional availability, food safety, nutrition, and sustainability, with community members, regional stakeholders, and experts in user experience design and web development. We conducted 48 interviews with a variety of people over 3 iterative cycles, assessing the prototype's ease of use with a validated measure, the System Usability Scale.Results. Community members, regional stakeholders, and other experts identified problematic elements in initial versions of the website (e.g., confusing symbols). We resolved issues and added features people identified as useful. Usability scores reached "best imaginable" for both the second and the third versions and did not differ significantly between sociodemographic groups. The final prototype includes a tool to explore each species and index cards to regroup accurate evidence relevant to each species.Conclusions. Engaging co-designers with different sociodemographic characteristics brought together a variety of perspectives. Several components would not have been included without co-designers' input; other components were greatly improved thanks to their feedback. Co-design approaches in research and intervention development are preferable to foster the inclusion of a variety of people. Once the prototype is programmed and available online, we hope to evaluate the website to determine its effects on food choices. Graphical Abstract This is a visual representation of the abstract. Highlights: Due to factors including cost, loss of traditional knowledge, and concerns about environmental contaminants, people living in coastal communities along the St. Lawrence River in Eastern Québec rarely consume local edible marine resources such as fish, seafood, plants, and mammals. Community members identified a need for a locally relevant website to support informed decision making about consuming local marine resources. By co-designing with community members, regional stakeholders, and other experts from the beginning of the process, we were able to integrate diverse perspectives into a website prototype adapted to community members' needs, with information about seasonal and regional availability, food safety, nutrition, and sustainability.